Prediction of birth weight before delivery according to characteristics of mothers at Fatemieh Hospital in Hamedan - Ahmadi Doolabi, M; Refaei, M; Shikhan, Z; Alavi Majd, H (Advances in Nursing & Midwifery, 2010)
Background and aim Fetal weight is an important factor in delivery since many preventable risks can be detected by accurate estimation of it before delivery. Accordingly, the risk of death and maternal as well as neonatal complications related to birth weight can be reduced by quick referral to more equipped centers. The aim of this study was to determine prediction of birth weight before delivery according to characteristics of mothers at Fatemieh Hospital in Hamedan. Materials and Methods In this descriptive-correlational study, 220 women with no complication in pregnancy and gestational age between 37-41 weeks were selected by convenience sampling. A questionnaire, a checklist, a meter band and a scale were used for data collection. The first 2 were validated by content method. The scale was validated with 2 standard scales, 1 with the brand of Rasa calibrated by Farid engineering Co. made in Iran for weighing mothers and the other with the band of Seca made in Germany. To validate the band, a standard, firm, flexible and inextensible one was used. Test-retest was applied for the reliability of the questionnaire and inter-rater method for the checklist and the meter band. The scales were also made reliable with appropriate protocol. A multiple regression analysis was performed to evaluate predictive value of characteristics in 10 pregnant mothers including weight, height, gestational weight gain, body mass index, fundal height, abdominal girth, arm girth, gestational age and fetal sex to identify an optimal combination for estimating birth weight. Data were analyzed by SPSS 11/5. Findings Of 10 factors under investigation, 4 including gestational age, height of mother, fundal height and fetal sex explained in combination the birth weight up to 44%. Press index showed that the following equation has proper prediction accuracy: Birth weight (g) =-2643.91+8.02 (gestational age in day) + 844.46 (mother’s height) (m) +65.23 (fundal height) (cm) +144.25 (fetal sex) (boy=1, girl=0) Conclusion Birth weight can be correctly estimated with the resulted regression equation in terms of maternal characteristics before delivery. Keywords: Prediction, Birth weight, Characteristics of pregnant mother, Delivery. *Corresponding Author: Mahboobeh Ahmadi Doolabi .Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences and Health services, Tehran, Iran E-mail: mah1372@yahoo.com